Vorläufige Ergebnisse von 99mTc-HMPAO-SPECT-Untersuchungen bei endogenen Psychosen - Wilhelm, K.-R.; Schröder, J.; Henningsen, H.; Sauer, H.; Georgi, P. (Nuklearmedizin - NuclearMedicine, 1989)
18 psychopharmacologically treated patients (7 schizophrenics, 5 schizoaffectives, 6 depressives) were studied using 99mTc-HMPAO-SPECT of the brain. The regional cerebral blood flow was measured in three transversal sections (infra-/supraventricular, ventricular) within 6 regions of interest (ROI) respectively (one frontal, one parietal and one occipital in each hemisphere). Corresponding ROIs of the same section in each hemisphere were compared. In the schizophrenics there was a significantly reduced perfusion in the left frontal region of the infraventricular and ventricular section (p < 0.02) compared with the data of the depressives. The schizoaffectives took an intermediate place. Since the patients were treated with psychopharmaca, the result must be interpreted cautiously. However, our findings seem to be in accordance with post-mortem-, CT- and PET-studies presented in the literature. Our results suggest that 99mTc-HMPAO-SPECT may be helpful in finding cerebral abnormalities in endogenous psychoses.